Timely extracorporeal membrane oxygenation assist reduces mortality after bypass surgery in patients with acute myocardial infarction. Issue 11 (16th September 2019) - Hamiko, Marwan; Slottosch, Ingo; Scherner, Max; Gestrich, Christopher; Wahlers, Thorsten; Putensen, Christian; Mellert, Fritz; Treede, Hendrik; Dewald, Oliver; Duerr, Georg Daniel
Abstract: Background: Patients with acute myocardial infarction (AMI) are at high risk when undergoing emergency coronary artery bypass graft (CABG)‐surgery. Their outcome remains poor despite increased use of extracorporeal membrane oxygenation (ECMO). We investigated the impact of timing for perioperative ECMO‐support in these patients. Methods: In this retrospective double‐center study, we evaluated 201 patients with AMI undergoing CABG, dividing them into the following groups: No‐ECMO (n = 101), preoperative ECMO (pre‐ECMO, n = 6), intraoperative ECMO (ECC‐ECMO, n = 67), and postoperative ECMO (post‐ECMO, n = 27). We evaluated the impact of ECMO timing on postoperative mortality, organ function, and length of stay, comparing these to predicted outcome using different risk‐scores. Results: Post‐ECMO patients showed lowest 30‐day‐survival (40.7%), while earlier ECMO‐start was associated with better outcome (50.7% in extracorporeal circulation [ECC]‐ECMO and 66.7% in pre‐ECMO patients). On admission, only pre‐ECMO and ECC‐ECMO patients showed higher surgery‐ and intensive‐care‐unit (ICU)‐related risk‐scores. In pre‐ and ECC‐ECMO patients, the first significant increase in lactate‐levels (>4 mmol/L) was observed preoperatively, while this occurred 1 hour postoperatively in post‐ECMO patients. Bilirubin was increased in all patients, decreasing after 3 and 12 days in pre‐ and ECC‐ECMO patients, respectively, but only after 18 days in post‐ECMO patients. Multiple ICU risk‐scores did not discriminate survival‐probability correctly. Only the ECMO‐related survival after veno‐arterial‐ECMO‐score correctly predicted the significantly lower survival in post‐ECMO patients. Conclusion: Our study shows that timely ECMO‐support is associated with earlier bilirubin‐downtrend and higher survival in patients with AMI after CABG. Lactate‐increase greater than 4 mmol/L seems to be a helpful threshold to trigger the timely onset of ECMO‐therapy, providing better survival.